Enhanced Extracellular Glutamate and Dopamine in the Ventral Pallidum of Alcohol-Preferring AA and Alcohol-Avoiding ANA Rats after Morphine - Kemppainen, Heidi; Nurmi, Harri; Raivio, Noora; Kiianmaa, Kalervo (Frontiers in Psychiatry, 2015)
The purpose of the present study was to investigate the role of ventral pallidal opioidergic mechanisms in the control of ethanol intake by studying the effects of acute administration of morphine on the levels of GABA, glutamate, and dopamine in the ventral pallidum. The study was conducted using the alcohol-preferring AA (Alko Alcohol) and alcohol-avoiding (Alko Non-Alcohol) rat lines that have well-documented differences in their voluntary ethanol intake and brain opioidergic systems. Therefore, examination of neurobiological differences between the lines is supposed to help to identify the neuronal mechanisms underlying ethanol intake, since selection pressure is assumed gradually to lead to enrichment of alleles promoting high or low ethanol intake, respectively. The effects of an acute dose of morphine (1 or 10 mg/kg s.c.) on the extracellular levels of GABA and glutamate in the ventral pallidum were monitored with in vivo microdialysis. The concentrations of GABA and glutamate in the dialysates were determined with a HPLC system using fluorescent detection, while electrochemical detection was used for dopamine. The levels of glutamate in the rats injected with morphine 1 mg/kg were significantly above the levels found in the controls and in the rats receiving morphine 10 mg/kg. Morphine 10 mg/kg also increased the levels of dopamine. Morphine could not, however, modify the levels of GABA. The rat lines did not differ in any of the effects of morphine. The data suggest that the glutamatergic and dopaminergic systems in the ventral pallidum may mediate some effects of morphine. Since there were no differences between the AA and ANA lines, the basic hypothesis underlying the use of the genetic animal model suggests that the effects of morphine detected probably do not underlie the different intake of ethanol by the lines and contribute to the control of ethanol intake in these animals.